Reforming Teaching to Cultivate Students’ Adaptability (Journal of Global Humanities and Social Sciences, 2024)
Talents in the new century should process independent spirits. Adaptability is the ability to make quick judgments and respond to changes when new situations and problems arise. In this era of change, only students with strong adaptability can keep up with the times. By cultivating adaptability, students will not only be helped to find solutions in the face of difficulties and learn to overcome difficulties, but also enhance their survival and development. Adaptability is a concentrated reflection of the abilities of contemporary students.